Assessment of patients who presented to the emergency department with mushroom poisoning. (July 2015) - Colak, S; Kandis, H; Afacan, MA; Erdogan, MO; Gunes, H; Kaya, E; Akdemir, HU; Saritas, A
Objective: This study aimed to assess the demographic characteristics, emergency department (ED) complaints, laboratory findings, and latent phase periods of patients who presented to the ED due to mushroom poisoning (MP) as well as the efficacy of conventional and hemofiltration therapies. Method: The study was conducted on patients who presented to the ED with MP between 2010 and 2012. The patient's demographic characteristics, complaints at the ED, latent phases, laboratory findings, and treatments of MP cases were evaluated. Results: The mean age of patients was 38.03 ± 15.96, where 63.8% of them were female and 36.2% were male. Visits occurred most frequently in the autumn (32.6%). When presenting to the ED, the most frequent complaint was nausea–vomiting. The aspartate aminotransferase (AST), alanine aminotransferase (ALT), international normalised ratio (INR), and blood urea nitrogen values of patients with a latent phase between 0 h and 5 h were significantly lower than the values of patients with a latent phase between 6 h and 24 h. In this study, 62% of the patients ( n = 36) had stomach lavage and received activated charcoal. Altogether, 55.2% of the patients had received conventional therapy, 37.9% of them received hemofiltration, and all of them received supportive treatment. The AST, ALT, and INR values of those who had received hemofiltration and conventional therapies were significantly higher than of those who received only supportive treatment ( p < 0.01). Conclusion: Hemofiltration, in combination with conventional therapy, seems to be an effective treatment for reducing mortality in suspected MP cases involving late acting toxins.